Hypotonic stress enhances colon cancer cell death induced by platinum derivatives and immunologically improves antitumor efficacy of intraperitoneal chemotherapy. Issue 11 (28th August 2019) - Demontoux, Lucie; Derangère, Valentin; Pilot, Thomas; Thinselin, Chloé; Chevriaux, Angélique; Chalmin, Fanny; Bouyer, Florence; Ghiringhelli, François; Rébé, Cédric
Abstract : Colorectal cancer is a highly metastatic disease that could invade various distal organs and also the peritoneal cavity leading to peritoneal carcinomatosis. This is a terminal condition with poor prognosis and only palliative treatments such as cytoreductive surgery and intraperitoneal chemotherapy are proposed to some patients. However, clinicians use different parameters of treatments without any consensus. Here we decided to evaluate the effect of osmolarity in the efficacy of this procedure to kill colon cancer cells. We first show that a short exposure of platinum derivatives in hypotonic conditions is more efficient to decrease cell viability of human and murine colon cancer cells in vitro as compared to isotonic conditions. This is related to more important incorporation of platinum and the capacity of hypotonic stress to induce the copper transporter CTR1 oligomerization. Oxaliplatin in hypotonic conditions induces caspase‐dependent cell death of colon cancer cells. Moreover, hypotonic conditions also modulate the capacity of oxaliplatin and cisplatin (but not carboplatin) to induce immunogenic cell death (ICD). In vivo, oxaliplatin in hypotonic conditions increases CD8 + T cell tumor infiltration and activation. Finally, in a murine peritoneal carcinomatosis model, oxaliplatin in hypotonic conditions is the only tested protocol which is able to slow down the appearance of tumor nodules and increase mice survival, while showing no effect in CD8 + T cells depleted mice or in immunodeficient mice. Altogether, our study provides new information both in vitro and in a preclinical model of peritoneal carcinomatosis, which highlights the importance of hypoosmolarity in intraperitoneal chemotherapy. Abstract : What's new? Colorectal cancer can lead to peritoneal carcinomatosis, a terminal condition with only palliative treatments such as intraperitoneal chemotherapy currently available. To date, no consensus on treatment parameters exists. Here, hypotonic stress improves platinum derivatives‐induced cell death in human and murine colon cancer cell lines. A short exposition of cancer cells to oxaliplatin in hypotonic conditions was sufficient to induce immunogenic cell death. In a peritoneal carcinomatosis model, hypotonic conditions induced mice survival in a CD8 + T cell‐dependent manner. The findings suggest that oxaliplatin in hypotonic conditions, in the absence of hyperthermia, should be considered by surgeons practicing intraperitoneal chemotherapy.